Retroauricular Approach for Targeted Cochlear Therapy Experiments in Wistar Albino Rats - Selçuk Mülazımoğlu (Balkan Medical Journal, 2017)
Background: As the idea of stem cell technology in the treatment of sensorial hearing loss has emerged over the past decades, the need for in vivo models for related experiments has become explicit. One of the most common experimental models for inner ear stem cell delivery experiments is the Wistar albino rat. Aims: To investigate the surgical anatomy of the temporal bone of the Wistar albino rat with respect to the dissection steps, operative techniques and potential pitfalls of surgery. Study Design: Animal experimentation. Methods: Adult Wistar albino rats were operated on via the retroauricular approach under an operation microscope. The anatomy of the temporal bone, the surgical route to the temporal bulla and the inner ear were investigated. Technical details of surgical steps, complications and potential pitfalls during the surgery were noted. Results: The study group consisted of 40 adult Wistar albino rats. The mean times to reach the bulla and to achieve cochleostomy were 4.3 (2-13 min) and 7.5 min (3.5-22 min), respectively. The mean width of the facial nerve was 0.84 mm (0.42-1.25 mm). The stapedial artery lay nearly perpendicular to the course of the facial nerve (88-93 °C). There were three major complications: two large cochleostomies and one massive bleed from the stapedial artery. Conclusion: The facial nerve was the key anatomical landmark in locating the bulla. By retrograde tracing of the facial nerve, it was possible to find the bulla ventral (inferior) to the main trunk. The facial nerve trunk was the upper limit when drilling the bulla. By dissecting the main trunk of the facial nerve and retracting cranially, a large drilling space could be achieved. Our results suggest that the retroauricular approach is an effective, feasible route for inner ear drug delivery experiments in Wistar albino rats